CHINA’S MIDDLE EAST POLICY AND PAKISTAN’S STRATEGIC CONCERNS - Humayun Zia Chohan; Ehsanullah Khan; Dr. Muhammad Fahim Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
The Middle East and China are the two regions that most people are now interested in. Even if the Middle East has descended into an intellectual conflict over Islamic fundamentalism, the hunt for new energy sources is still vital. China’s policy framework, centered on non-interference, economic development, and the pursuit of a multipolar global environment, poses a strong challenge to the United States, which advocates for democracy and human rights while pursuing an interventionist foreign policy. Right now, the world’s most powerful economies are competing fiercely for energy resources, and the same is true for oil and gas. China is the world’s second-largest oil consumer, behind the United States (Bajpaee, 2006). China is seeking to strengthen its military, political, and economic might in the region without using force. Many predict that Saudi Arabia, China, and Russia will establish a new global power triangle because of their interdependencies, even if much more will become clear in the future. With a major focus on their bilateral ties, this article explores China’s Middle East policy, its expanding influence in the region, and its implications for Pakistan. China is now taking a wait-and-see stance. Pakistan’s future connections with the Middle East are greatly worried due to the intricate and multifaceted nature of the "Arc of crisis" in the area. Pakistan’s neutral position on this matter exposes it to serious dangers, opportunities, and security concerns.